Water a comprehensive treatise : volume 4 aqueous solutions of amphiphiles and macromolécules - Frank, Felix (New York : Plenum Press, 1975)
This volumen of wáter s comprehensive treatise is devoted to aqueous solutios of macromolecules and aqueous systems of smal molecules which exhibit reversible aggregation in solution.
Chapter 1. The hydrophobic interaction Chapter 2. Surfactants Chapter 3. Dyestuffs Chapter 4. Lipids Chapter 5. Nucleic Acids, peptides and prteins
index references, autor index,subject index, compound index
Keywords: MACROMOLECULES; SOLUTION (CHEMISTRY)